Efeitos do novo nitrato orgânico 4-clorobenzoato de 4-nitrooxibutila sobre a função vascular da artéria mesentérica superior de ratos - Ruiz, Clara Rittmeyer (2024)
Normal vascular function depends on the balance between the endothelial production of vasodilating and constricting factors. The endothelial dysfunction can be characterized by reduced bioavailability of vasodilators such as nitric oxide (NO). Organic nitrates are NO-donating drugs and potent vasodilators. Therefore, this work aims to investigate the mechanism of action of a new organic nitrate, 4-nitrooxybutyl 4-chlorobenzoate (4ClBN), on the vascular function of the superior mesenteric artery of Wistar rats (Rattus norvegicus). To this end, the experimental protocols carried out were conducted using the organ bath. Superior mesenteric artery rings were isolated using aerated Tyrode nutrient solution with a carbogenic mixture at a temperature of 37°C. After one hour of stabilization, the viability of the rings was checked and the endothelium test was performed. Next, pre-contraction was performed using phenylephrine (PE) and a concentration-response curve was performed using 4ClBN to evaluate the vasorelaxant effect. 4ClBN was able to evoke a vasorelaxant response in rings with endothelium (Emax=103.1±3.9; pD2=6.68±0.09) and without endothelium (Emax=114.7±4, 2; pD2=6.64 ±0.08). From then on, all protocols were performed with rings without functional endothelium. Potency was reduced in rings pre-contracted with 60 mM KCl (pD2=5.18±0.03; p<0.05 vs FEN). Potency was reduced in the presence of L-NAME (NOS inhibitor, 100 μM) (pD2 5.52 ± 0.02, p<0.05 vs FEN; Emax 109.0 ± 0.95). The potency and efficacy were reduced in the presence of HDX (radical NO scavenger, 100 μM) (Emax=74.05±6.22 and pD2=4.08±0.06; p<0.05 vs FEN) and ODQ (GCs inhibitor, 10 μM) (Emax=96.84±10.86 and pD2=3.69±0.06; p<0.05 vs FEN). When incubating the rings with 20 mM KCl and 3 mM TEA the potency was reduced (5.35±0.05 and 5.03±0.04, respectively p<0.05 vs FEN). When investigating the subtypes of potassium channels involved in vasorelaxation induced by 4ClBN, a reduction in potency was observed when carrying out experimental protocols blocking Kir (5.79±0.08; p<0.05 vs FEN), Kv (5 .06±0.04; p<0.05 vs FEN), Bkca (5.06±0.12; p<0.05 vs FEN) and KATP (6.30±0.07; p<0.05 vs FEN). Finally, an ex vivo pharmacological tolerance test was carried out and a reduction in the potency (5.19±0.07; p<0.05 vs FEN) of 4ClBN was observed in rings pre-exposed to the compound. Thus, we suggest that the vasorelaxant response induced by 4ClBN is effective in the presence and absence of endothelium, is effected by the mechanism of NO donation and activation of the NO/GCs pathway and has the participation of Kir, Kv, BKca and Katp type potassium channels. . Furthermore, the molecule induced pharmacological tolerance ex vivo.